2006
DOI: 10.1212/01.wnl.0000223332.35936.6e
|View full text |Cite
|
Sign up to set email alerts
|

Medication-overuse headache in patients with cluster headache

Abstract: Medication-overuse headache is a previously underrecognized and treatable problem associated with cluster headache (CH). CH patients should be carefully monitored, especially those with a personal or family history of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 66 publications
5
76
0
4
Order By: Relevance
“…A recent, population-based study [34] found that the use of barbiturates or opiates led to an increased risk of developing transformed migraine. Such data were consistent with earlier clinicbased studies in which migraine patients treated with opioids for other biological or pain issues were likely to develop transformed migraine [35][36][37]. Hence, extreme caution should be the rule in the use of opioids or butalbital agents in migraine patients (even for other medical issues).…”
Section: Behavioral Assessmentsupporting
confidence: 88%
“…A recent, population-based study [34] found that the use of barbiturates or opiates led to an increased risk of developing transformed migraine. Such data were consistent with earlier clinicbased studies in which migraine patients treated with opioids for other biological or pain issues were likely to develop transformed migraine [35][36][37]. Hence, extreme caution should be the rule in the use of opioids or butalbital agents in migraine patients (even for other medical issues).…”
Section: Behavioral Assessmentsupporting
confidence: 88%
“…Ez különösen abban az esetben jelentős, ha migrénben vagy tenziós fejfájásban szenvedő betegek szednek rendszeresen, nagy adagban fájdalomcsillapító-kat [10], még akkor is, ha más betegség miatt szedik ezeket a gyógyszereket [26]. Jóval ritkábban, de előfordul FTTF olyan betegek körében is, akik korábban nem voltak fejfájósok, de családjukban többeknek volt migrénje [27]. Nem elhanyagolható a pszichológiai kockázati té-nyezők szerepe sem: az anticipátoros szorongás, illetve a hangulatzavar is hozzájárulnak a gyógyszerek túlzott mértékű fogyasztásának kialakulásához, illetve annak fenntartásához.…”
Section: Kockázati Tényezőkunclassified
“…14,120 Within this group of MOH patients, the vast majority first present with episodic migraine or tension-type headache 121 as opposed to other forms of primary headache such as cluster headache. 122 We hypothesise this selective propensity to develop MOH stems from altered pro-inflammatory central immune signalling in patients with migraine and tension-type headache, or the presence of underlying central sensitisation, which renders them particularly susceptible to the effects of opioid-induced glial activation.…”
Section: Pro-inflammatory Central Immune Signalling Hypothesis Of Mohmentioning
confidence: 99%